Water Diffusion from a Bacterial Cell in Low‐Moisture Foods. Issue 9 (9th August 2016) - Syamaladevi, Roopesh M.; Tang, Juming; Zhong, QingPing
Abstract: We used a Fick's unsteady state diffusion equation to estimate the time required for a single spherical shaped bacterium (assuming Enterococcus faecium as the target microorganism) in low‐moisture foods to equilibrate with the environment. We generated water sorption isotherms of freeze‐dried E. faecium . The water activity of bacterial cells at given water content increased considerably as temperature increased from 20 to 80 °C, as observed in the sorption isotherms of bacterial cells. When the water vapor diffusion coefficient was assumed as between 10 −12 and 10 −10 m 2 /s for bacterial cells, the predicted equilibration times ( t eq ) ranged from 8.24×10 −4 to 8.24×10 −2 s. Considering a cell membrane barrier with a lower water diffusion coefficient (10 −15 m 2 /s) around the bacterial cell with a water diffusion coefficient of 10 −12 m 2 /s, the t eq predicted using COMSOL Multiphysics program was 3.8×10 −1 s. This result suggests that a single bacterium equilibrates rapidly (within seconds) with change in environmental humidity and temperature.